Pemanfaatan Aplikasi Toontastic 3D sebagai Media Interaktif untuk Meningkatkan Keterampilan Menulis Narasi Siswa SMAN 5 Ambon - Hukom, Salmon James; Que, Stella Rose (Universitas Pattimura, 2024)
This community service activity aims to improve the narrative writing skills of high school students through the use of the Toontastic 3D application as an interactive learning medium. The targets of the activity are grade X students at SMA Negeri 5 Ambon who have challenges in developing ideas and narrative writing structures. Theoretically, this activity is based on the constructivist learning approach and the theory of multiple intelligences, which emphasizes the importance of active student involvement and the use of media that suits visual and kinesthetic learning styles. Toontastic 3D, as an animation-based digital media, provides opportunities for students to creatively organize and develop storylines while strengthening their narrative cohesion and coherence. The method of activity implementation includes socialization, training on the use of the application, assistance in writing animation-based narratives, and reflection sessions. The evaluation was conducted through questionnaires that were analyzed quantitatively and qualitatively. The results of the questionnaire analysis from 30 respondents showed that 87% of students felt more motivated in writing after using Toontastic 3D, 83% stated that this media helped them in organizing the story structure (introduction, conflict, climax, and resolution), and 78% claimed to be more confident in expressing their ideas in writing. In addition, students reported that the visual and interactive learning experience made the writing process more enjoyable and meaningful. Based on these results, it can be concluded that the integration of interactive digital media such as Toontastic 3D is an effective approach to support the improvement of narrative writing literacy among secondary school students. This activity also encourages innovation in Indonesian language learning through the use of technology that suits the characteristics of the digital generation.